Morphological change in peristaltic crawling motion of a narrow pipe inspection robot inspired by earthworm's locomotion. (3rd April 2018) - Kamata, M.; Yamazaki, S.; Tanise, Y.; Yamada, Y.; Nakamura, T.
Abstract: Infrastructure pipes require inspection in order to prevent accidents. However, it is difficult to inspect a 1-in-diameter gas pipe because it is long, narrow and complicated. Therefore, an earthworm-type robot was developed to inspect this 1-in pipe. The robot moved by peristaltic crawling with pneumatic artificial muscles and displayed its suitability as a 1-in pipe inspection robot in experiments. However, its speed was extremely slow to be practically utilized. A major cause for this is the small distance covered in a single motion of the robot. Therefore, in this study, we developed an axial extension actuator to increase the moving distance of the robot in a single motion. Furthermore, we installed this new actuator on our robot and made it possible for the robot to change the morphological motion in peristaltic crawling. The experiments with straight and elbow pipes ascertained the importance of morphological change in peristaltic crawling for increasing the speed of the robot. Moreover, in a continuous elbow pipe, the velocity of the proposed robot was 5.5 mm/s, which is 1.3 times faster than that of the conventional robot. Consequently, we confirmed that the speed of the proposed robot was sufficiently fast for inspecting a 1-in pipe. Abstract :